Novel liquid precursor-based facile synthesis of large-area continuous, single, and few-layer graphene films - Srivastava A.; Galande C.; Ci L.; Song L.; Rai C.; Jariwala D.; Kelly K.F.; Ajayan P.M. (My University, 2025)
Graphene has attracted a great deal of attention because of its unique band structure and electronic properties that make it promising for applications in next-generation electronic devices, transparent flexible conducting electrodes, and sensors. Here, we report the substrate selective growth of centimeter size (·∼3.5 cm × 1.5 cm), uniform, and continuous single and few-layer graphene films employing chemical vapor deposition technique on polycrystalline Cu foils using liquid precursor hexane. Structural characterizations suggest that as-grown graphene films are mostly single and few layers over large areas. We have demonstrated that these graphene films can be easily transferred to any desired substrate without damage. A liquid-precursor-based synthesis route opens up a new window for simple and inexpensive growth of pristine as well as doped graphene films using various organic liquids containing the dopant atoms. © 2010 American Chemical Society.